Evaluation of 'TBDetect' sputum microscopy kit for improved detection of Mycobacterium tuberculosis: a multi-centric validation study. (June 2021) - Anthwal, Divya; Gupta, Rakesh Kumar; Gomathi, Narayan Sivaramakrishnan; Tripathy, Srikanth Prasad; Das, Dasarathi; Pati, Sanghamitra; Panwalkar, Nikita; Desikan, Prabha; Bala, Kiran; Singh, Urvashi B.; Bhalla, Manpreet; Singhal, Ritu; et al.
Abstract: Objectives: The present study aimed to evaluate the performance of the 'TB Detect ' kit-based bio-safe fluorescent microscopy filter (BioFM-Filter) microscopy in comparison with direct smear microscopy and culture for the detection of pulmonary tuberculosis (TB) in a multi-centric setting in India. Methods: The TB Detect kit enables sputum concentration through filtration using the BioFM-Filter for improved and bio-safe smear microscopy. We evaluated the performance of the TB Detect kit in a six-site multi-centric validation study on sputum collected from 2086 presumptive TB patients. Results: The combined positivity of TB Detect microscopy performed on these sputum samples was 20% ( n  = 417/2086) vs 16.1% of light-emitting diode fluorescence microscopy (LED-FM, n  = 337/2086) and 16% of Ziehl Neelsen (ZN) smear microscopy ( n  = 333/2086). The increment in positivity of TB Detect over both LED-FM and ZN smears was significant (p < 0.001). The overall sensitivity of TB Detect for six sites was ~55% (202/367, 95% confidence interval (CI): 50, 60%) vs 52% (191/367, 95% CI: 47, 57%) for LED-FM (p 0.14) and 50.9% (187/367, 95% CI: 46, 56%) for ZN smear (p < 0.05), using Mycobacterium Growth Indicator Tube culture (MGIT, n  = 1949, culture positive, n  = 367) as the reference standard. A bio-safety evaluation at six sites confirmed efficient sputum disinfection by TB Detect ; 99.95% samples (1873/1874) were sterile after 42 days of incubation. Scientists and technicians at the study sites indicated the ease of use and convenience of TB Detect microscopy during feedback. Conclusions: TB Detect added value to the smear microscopy test due to its improved performance, convenience and user safety. These findings indicate that equipment-free TB Detect technology has the potential to improve TB diagnosis in basic laboratory settings by leveraging on the existing nationwide network of designated microscopy centres and primary healthcare centres.